CURRENT PROBLEMS OF PUBLIC DEBT AND SOVEREIGN DEFAULTS TO THE EU COUNTRIES - E. A. Zvonova (Финансы: теория и практика, 2017)
Today the threat of sovereign defaults is relevant and severe enough not only to developing but also to developed countries. In the first half of the 1980s, the global crisis of emerging markets external debt demonstrated for the first time that the debt crisis, as well as currency, banking, securities and other financial crises, can be not only sovereign, but also global and lead to the need for restructuring the entire global financial and monetary system. In 2000-2010, it became evident that developed countries were subject to the debt crisis not only at sovereign level but also at the level of integrated monetary and financial groups. The problem of debt crisis is the most acute in the EU countries. In this context, the analysis of the current state of external debt of the EU countries and possible effects of sovereign defaults in peripheral countries on the euro area seems relevant both from the point of reforming the global financial architecture, as well as in view of the position of Russia in this reform. The article considers the following issues: classification of modern defaults, restructuring of the external debt, default dependence and exchange rate fluctuations. It also investigates the problems of debt restructuring and tightening of international credit conditions. The author examines the external debt indicators of EU countries and the probability of sovereign defaults in EU peripheral countries as well as considers the debt stability criteria for euro zone economies and analyzes potential consequences of defaults in the EU area for the global financial market.